2015
DOI: 10.7600/jpfsm.4.369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clenbuterol enantiomers on growth of young male rats

Abstract: Clenbuterol (CB) is one of the β 2 -adrenergic receptor agonists with powerful muscle anabolic and lipolytic effects, and is prohibited as a doping drug for athletes. However, it is one of the candidate countermeasures for aging-related diseases. Previously we reported that CB induced muscular hypertrophy, but inhibited the longitudinal growth of bones in young male rats. However, the mechanism of the inhibitory effect on bone growth is not yet clear. CB is manufactured as a 1:1 racemic mixture of 2 isomers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The difference in the enantiomeric relationship of the drug group could be explained by the biological activity of the enantiomers. It has been described that β‐agonists with chiral structures have different metabolism, being R‐(─) enantiomers more active than S‐(+) forms, which suggests that S‐(+) clenbuterol is less metabolized and excreted . It is possible that the drug metabolism is time– and concentration–dependent, leading to its disappearance in the last days (6 and 7 days) when the concentration of clenbuterol is low.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in the enantiomeric relationship of the drug group could be explained by the biological activity of the enantiomers. It has been described that β‐agonists with chiral structures have different metabolism, being R‐(─) enantiomers more active than S‐(+) forms, which suggests that S‐(+) clenbuterol is less metabolized and excreted . It is possible that the drug metabolism is time– and concentration–dependent, leading to its disappearance in the last days (6 and 7 days) when the concentration of clenbuterol is low.…”
Section: Resultsmentioning
confidence: 99%
“…It has been described that β-agonists with chiral structures have different metabolism, being R-(─) enantiomers more active than S-(+) forms, which suggests that S-(+) clenbuterol is less metabolized and excreted. 30 It is possible that the drug metabolism is time-and concentration-dependent, leading to its disappearance in the last days (6 and 7 days) when the concentration of clenbuterol is low. In a previous work, the pharmacokinetics of clenbuterol enantiomers in rats after i.v.…”
Section: Application Of the Methods In The Experimental Animal Modelmentioning
confidence: 99%
“…The activity was monitored by measuring the tissue mass and determining the protein content. The results showed that both stereoisomers had the same anabolic activity, but (S)-(+)-clenbuterol exhibited a significant increase in the mass of the heart muscle [44].…”
Section: Introductionmentioning
confidence: 95%